Compensation for Loss of an Economic Nature : An Australian Perspective - Luntz, Harold (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1998)
This paper first describes briefly the scope of the no-fault motor accident schemes which operate in Australia. It then sets out and evaluates the benefits payable under each for losses of an economic nature. These are benefits for hospital, medical, nursing, rehabilitation and like needs created by injuries in a motor accident ; for informal nursing services and assistance in the home, the need for which is similarly created ; for loss of earning capacity resulting from such accidents ; and for death so resulting. It does not deal with benefits for loss of a non-economic nature, such as pain and suffering (for which, as such, compensation is not generally payable under the schemes) and impairment. It nevertheless concludes that most benefits for loss of an economic nature should be integrated with the Australian social security system and that the true role of a no-fault scheme is to compensate for permanent impairment, since there is no general disability benefit payable under the social security system.